A Study of the Sources of Environmental Noise at the University of Education Winneba, South Campus Library (SCL) - Adzobu, Joseph (Ghana Library Journal, 2003)
Noise is generated in libraries as staff, and users move about, interact, and use equipment to retrieve information or copy text. Noise in the communication process interrupts message delivery. This study identifies inadequate space as the main inherent causative factor of noise generation at SCL. Management of scarce library space has resulted in the provision of inadequate usertraffic-space, which enhances interruption of seated users by moving users in areas of desk-shelf intercalation. Space limitation also made it impossible for Library Management to provide separate space for group work - another noise factor. Fortunately, extensions are being made to the Library; this should allow Management to take steps to mitigate the major inherent noise factors.